2023
DOI: 10.1038/s41586-022-05666-1
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional fossil preservation and evolution of the ray-finned fish brain

Abstract: Brain anatomy provides key evidence for ray-finned fish relationships 1 , but two key limitations obscure our understanding of neuroanatomical evolution in this major vertebrate group. First, the deepest branching living lineages are separated from the group's common ancestor by hundreds of millions of years, with indications that aspects of .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The authors also found that specimens can be stained in small groups with little noticeable reduction in stain duration relative to specimens soaked individually. Their own experiences, however, lead them to recommend that when staining many specimens, it is best to do so in smaller (Figueroa et al, 2023;Kolmann et al, 2018). This is beneficial from a logistical standpoint, as many research groups do not have exclusive access to a CT scanner.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found that specimens can be stained in small groups with little noticeable reduction in stain duration relative to specimens soaked individually. Their own experiences, however, lead them to recommend that when staining many specimens, it is best to do so in smaller (Figueroa et al, 2023;Kolmann et al, 2018). This is beneficial from a logistical standpoint, as many research groups do not have exclusive access to a CT scanner.…”
Section: Discussionmentioning
confidence: 99%
“…As exemplified by the predicted ancestral mosaic brain pattern and the failure of well-preserved D. patagonica endocast to represent the morphology of midbrain and hindbrain regions, we revealed the power of combining extant and extinct species, soft tissue reconstructions, and osteological traits in tracing brain evolution, ecomorphology, and the ecological origins of snakes from a neurobiological perspective. Furthermore, our study provides an alternative holistic framework that can be reinforced by the inclusion of additional key basal fossorial alethinophidian extant taxa, such as tropidophiids and uropeltids ( 38 ), as well as future paleontological discoveries, including fossilized brains ( 30 ). Last, analysis of not only external but also internal brain features, including neuronal parameters such as morphology, spatial arrangement, and connectivity, can also improve the robustness of our framework.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advances, early snake evolution has remained enigmatic, and different perspectives are essential to illuminate stem snake lineages and infer ancestral ecological behaviors. In particular, because of the fragmentary nature of the oldest snake fossils from the Middle Jurassic-Lower Cretaceous (16), analysis of internal soft tissues not necessarily preserved in fossils (30) but tightly linked to functional and ecological demands in snakes has the potential to clarify these issues. Tracking brain-behavior relationships through the reconstruction of endocranial cavities (endocasts) in extant and extinct taxa (31) has been critical for unraveling major evolutionary transitions in vertebrates (32)(33)(34), including humans (35).…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear when, why and how everted telencephali emerged in actinopterygii. A recent study of the fossilized brain of the extinct ray-finned fish Coccocephalus wildi showed that this species seemed to have an evaginated brain (Figueroa et al, 2023), suggesting that an everted telencephalon might have evolved later than thought until now. Kappers was, to our knowledge, first to suggest in Kappers (1908) that eversion could happen as a consequence of lack of space within the skull.…”
Section: Why Does Eversion Occur?mentioning
confidence: 99%
“…This would force embryonic telencephalon to use all the available space within the skull, undergoing eversion instead of evagination to minimize ventricular volume (Striedter & Northcutt, 2006). However, results in the extinct C. wildi now challenges this theory, as it seems that this species had an evaginated telencephalon despite restricted available space within the skull (Figueroa et al, 2023).…”
Section: Why Does Eversion Occur?mentioning
confidence: 99%